Rasionalitas Indonesia Dalam Kebijakan Restriksi Ekspor Nikel Tahun 2020 (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2023)
Indonesia set a policy of limiting nickel exports in 2020 after going through dynamics that occurred in the nickel mining industry over the previous decades. Nickel Export Restriction policy is said to be Indonesia’s response to the Renewable Energy Directive policy issued by European Union which is detrimental to the Indonesian palm oil industry. This research aims to analyze and explain the rationality of Indonesia’s Government on the formation of a nickel restriction policy by explanatory-qualitative methods sourced from secondary data. The calculation of the rationality then explained further through the game theory matrix and nash equilibrium. The results of this research found that Indonesia issued Nickel Export Restriction policy is rational because it has more benefits than other policy alternatives. Keywords: Indonesia, Nickel Export Restriction, Rational Actor Model, Nash Equilibrium